THE EFFORT OF IMPROVING THE ACTIVITY AND ABILITY OF STUDENTS IN WRITING REVIEW TEXT THROUGH FILM AT SMA NEGERI 1 PUNGGUR CENTRAL LAMPUNG - Asih, Peni (Premise: Journal of English Education and Applied Linguistics, 2017)
The objectives of this classroom action research are to improve the students’ activity and ability in writing review text at class XII IPA 1 semester 2 of SMA N 1 Punggur. This research uses a film as a medium which is aimed to make the students of XII IPA 1 easy in writing a review text. The researcher uses two cycles in her research which consists of 2 meetings in each cycle. Cycle I   use a short story in its meeting and cycle II uses a film in its meeting. The result shows that the average score of students who gained passing grade (74) or above in cycle I is 56,67 % and in cycle II is 76,6 % while there is  43,33 % of students who get under 74 % in cycle I and 23,34%   in cycle II. It means that their average score in writing a review text using film has increased. The students have made good progress after being given treatment by using film as medium of instruction. This is because film can make the students active during the teaching learning process. The result of this study implies that the teaching learning process using film improves the students ‘ability in writing a review text. Therefore, this media is recommended to be used in the process of teaching learning English especially review text.